Identification of long non-coding RNAs in serum exosomes from colorectal cancer patients and effects of exosomes on tube formation by endothelial cells - Ng, Chin Tat (2019)
Extracellular vesicles (exosome-like vesicles) are small membrane vesicles ranging from 20-150nm in size that are released by various cells into the extracellular space. This extracellular vesicles play a major role in cell-to-cell communication and contain materials, such as proteins, mRNAs, microRNAs (miRNAs) and long non-coding RNAs (lncRNAs). Recent studies have reported that the components in exosomes vary based on the type of cell. Long non-coding RNAs (lncRNAs) are non-protein-coding RNAs consisting of more than 200 nucleotides in length. It has been shown that lncRNAs play an important role in various cellular processes including angiogenesis by interacting with RNA, DNA or proteins through diverse mechanisms to regulate gene expression. However, the effect of exosomes derived from an invasive colorectal cancer cell line on angiogenesis is unclear and the potential of lncRNAs in circulating exosomes as biomarkers have not been completely studied. Hence, the aims of this study is to investigate the effect of exosomes derived from an invasive colorectal cancer cell line on angiogenesis of endothelial cells and to identify the potential of lncRNAs in circulating exosomes as biomarkers for detection of colorectal cancer. In the present study, the exosomes from the cell culture supernatants of an invasive colorectal cancer cell line SW480-7 were characterized and lncRNAs in these exosomes were profiled. The effect on tube formation and expression of angiogenic genes in a microvascular endothelial cell, telomerase-immortalized microvascular endothelial cell (TIME) cocultured with exosomes were also determined. In addition, RT2 lncRNA PCR array was used for exosomal lncRNA profiling to determine the relative expression level of lncRNAs in the exosomes of sera from 18 CRC (colorectal carcinoma) and 21 non-cancer patients. The expression level of lncRNAs was compared between 8 early-stage (stages I and II) and 10 advanced-stage (stages III and IV) of CRC patients. Results showed that exosomes derived from SW480-7 increased tube formation and up-regulated expression FGFR3 mRNA in TIME. Zetasizer result showed average diameter of exosomes derived from SW480-7 was 274.6 nm and morphology analysis showed the majority of exosomes size less than 200 nm. Western blot analysis demonstrated that exosomes from SW480-7 contained exosomal protein, Alix. A total number of 32 lncRNAs were detected in SW480-7- derived exosomes and some have been reported to be associated with angiogenesis. In clinical studies, six lncRNAs, namely GAS5, H19, LINC00152, SNHG16, RMRP, and ZFAS1 were detected in the sera of 18 CRC patients. These lnRNAs may serve as potential biomarkers for detection of CRC. Among these six lncRNAs, expression level of LINC00152 was found to be significantly lower in CRC patients as compared to non-cancer patients (p=0.04). The expression level of lncRNAs was compared for early versus advanced-stage of CRC patients. Expression level of exosomal lncRNA H19 was significantly up-regulated in advanced-stage of CRC (p value= 0.04).In conclusion, exosomal lncRNAs derived from SW480-7 increased tube formation and up-regulated expression of FGFR3 mRNA in TIME. Among the six exosomal lncRNAs detected in the sera, LINC00152 and H19 may be useful as biomarkers in liquid biopsies for diagnosis and treatment monitoring in colorectal cancer.